Fireproof plate and preparation method thereof

By using materials such as magnesium oxide desulfurization waste slag, the problem of building boards reducing strength in high temperature environments is solved, and high-value utilization of industrial waste is achieved, and excellent compressive strength and fire resistance are obtained.

CN119707434AActive Publication Date: 2025-03-28SHANDONG RAILWAY INVESTMENT HLDG GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510228974.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

Existing building panels are prone to lose strength and even burst under high temperature environments, and industrial waste cannot be effectively utilized in resource-based manner, resulting in environmental pollution.

Method used

Magnesium oxide desulfurization waste slag is used as the main raw material, combined with light flammable magnesium oxide, heavy flammable magnesium oxide, potassium dihydrogen phosphate, ultrafine sulfated steel slag powder, red mud and other materials, and combined with steel slag coarse and fine aggregates and mixed fibers, a fireproof board with good fire resistance and compressive strength is formed through the hydration reaction of the gelling material.

Benefits of technology

The resource utilization of magnesium oxide desulfurization waste slag has been realized, the compressive strength and fire resistance of the fireproof board are improved, the volume deformation and mechanical performance losses after high temperature are reduced, and the process is simple and environmentally friendly is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707434A_ABST
    Figure CN119707434A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to a fireproof plate and a preparation method thereof.The fireproof plate is prepared by adopting magnesium oxide desulfurization waste residues, supplementing light calcined magnesium oxide and dead calcined magnesium oxide, adding monopotassium phosphate, superfine vulcanized steel slag powder and red mud as main active substances and adopting steel slag coarse and fine aggregates as all-solid waste aggregates; and the admixture and the hybrid fiber are matched to prepare the fireproof plate which has excellent compressive strength and fireproof effect and is environment-friendly and waste-utilizing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, in particular to a fireproof board and a preparation method thereof. Background Art

[0002] With the continuous development of construction and transportation engineering, more and more building boards are being used. For some partition walls, steel beam cladding, skirt walls, tunnel inner walls, underground projects, surrounding walls and other structures, calcium silicate boards, fiber reinforced cement boards and other building boards are often used.

[0003] However, although ordinary building boards such as calcium silicate boards are mainly made of inorganic materials and have excellent physical properties, processing performance and certain non-combustible characteristics, they are prone to lose strength or even burst in high temperature environments. Especially for cement products, when the temperature exceeds 800°C, the mechanical properties drop sharply, and cracks and peeling occur on the surface of the board, affecting the appearance and use effect.

[0004] A lot of industrial waste is generated during industrialization, which is usually stored on the surface or buried underground, which can easily cause environmental pollution. For example, desulfurization ash, red mud, etc. Some highly active industrial solid wastes such as fly ash, mineral powder, silica fume, etc. are often added to cement products as active admixtures and are well reused. Magnesium oxide desulfurization, as a new generation of desulfurization technology, has more advantages than calcium oxide desulfurization. The by-product is magnesium oxide desulfurization waste residue, whose main components are magnesium sulfate, magnesium hydroxide, unreacted magnesium oxide and some diatomaceous earth filter aids, etc. This waste residue has not yet been effectively utilized as a resource. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a fireproof board. Specifically, the present invention adopts magnesium oxide desulfurization waste residue, supplements light-burned magnesium oxide and heavy-burned magnesium oxide, and adds potassium dihydrogen phosphate, ultrafine sulfided steel slag powder, and red mud as main active substances, adopts steel slag coarse and fine aggregates as all-solid waste aggregates, and cooperates with admixtures and mixed fibers to prepare a fireproof board with excellent compressive strength and fireproof effect, which is environmentally friendly and waste-recycling.

[0006] Specifically, the fireproof board of the present invention is composed of the following raw materials in parts by weight: 190-200 parts of magnesium oxide desulfurization waste slag, 50-70 parts of light-burned magnesium oxide, 70-90 parts of heavy-burned magnesium oxide, 100-110 parts of potassium dihydrogen phosphate, 50-60 parts of ultrafine sulfided steel slag powder, 20-25 parts of red mud, 1080-1120 parts of steel slag coarse aggregate, 830-850 parts of steel slag fine aggregate, 5-6 parts of borax, 4-5 parts of glass fiber, 3-4 parts of basalt fiber, 3-5 parts of calcium sulfate whiskers, 7-10 parts of water reducer, and 158-165 parts of water.

[0007] According to the composition characteristics of magnesium oxide desulfurization waste residue, after a large number of tests, no modification treatment is required for the waste residue, and the waste residue is used as the main raw material to prepare a fireproof board, thereby realizing the resource utilization of magnesium oxide desulfurization waste residue. However, the mechanical properties of the product with magnesium oxide desulfurization waste residue as the main material are poor, and the slurry workability is poor during the preparation process, and a large number of tests and optimizations are required for other compound materials. Specifically, the present invention adopts magnesium oxide desulfurization waste residue, adds light-burned magnesium oxide and heavy-burned magnesium oxide, and adds potassium dihydrogen phosphate, and hydration produces a large amount of magnesium hydration products with good fireproof effect. In order to improve the mechanical properties and high temperature resistance of the fireproof board, after a large number of tests, ultrafine sulfide steel slag powder and red mud are added to supplement the magnesium-based hydration products, and the slurry workability can be combined, and the compound use effect is good.

[0008] The present invention adopts steel slag as coarse and fine aggregate, and combines glass fiber, basalt fiber and calcium sulfate whisker as mixed fiber, which can improve the high temperature resistance of the fireproof board, reduce the volume deformation and mechanical property loss of the fireproof board after high temperature, and has good use effect.

[0009] Preferably, the particle size of the magnesium oxide desulfurization waste slag is ≤45 μm.

[0010] Preferably, the light-burned magnesium oxide is prepared by calcining magnesite at 900-1000° C., and has a particle size of ≤75 μm.

[0011] Preferably, the dead-burned magnesium oxide is prepared by calcining magnesite at 1450-1500° C., and has a particle size of ≤45 μm.

[0012] Preferably, the ultrafine sulfided steel slag powder is prepared by sulfiding and grinding steel slag powder, and the particle size is ≤10μm. Steel slag is a byproduct of the steelmaking industry, and its mineral phase composition is similar to cement clinker, and it has certain activity, but its free calcium oxide content is high, which poses a potential safety hazard. The commonly used treatment methods are ultrafine grinding or carbonization, but the present invention has found in experiments that if ultrafine carbonized steel slag powder is used, the fire resistance stability of the product is slightly poor, while the fireproof board using ultrafine sulfided steel slag powder has a better high temperature resistance effect.

[0013] Preferably, the red mud particle size is ≤75 μm.

[0014] Preferably, the particle size of the steel slag coarse aggregate is 5-16 mm, and the particle size of the steel slag fine aggregate is 0.1-0.425 μm.

[0015] Preferably, the glass fiber has a diameter of 10-12 μm and a length of 12-14 mm, the basalt fiber has a diameter of 15-16 μm and a length of 10-12 mm, and the calcium sulfate whisker has a diameter of 2-6 μm and a length of 50-160 μm.

[0016] Preferably, the water reducer is a polycarboxylate water reducer.

[0017] The present invention also relates to a method for preparing the fireproof board, which specifically comprises the following steps: 1) Weigh each raw material by weight, 2) Mix all the raw materials evenly to obtain slurry. 3) Shape the slurry, demould and cure it.

[0018] More preferably, in step 2), firstly, the magnesium oxide desulfurization waste residue, light-burned magnesium oxide, heavily-burned magnesium oxide, potassium dihydrogen phosphate, ultrafine sulfide steel slag powder, red mud, borax, glass fiber, basalt fiber, and calcium sulfate whisker are uniformly mixed to obtain dry material, the water reducer and water are uniformly mixed to obtain liquid material, and then the dry material, steel slag coarse aggregate, steel slag fine aggregate, and liquid material are uniformly mixed to obtain slurry.

[0019] The present invention has the following technical advantages: 1. The present invention uses a large amount of magnesium oxide desulfurization waste residue, ultrafine sulfided steel slag powder, and red mud as active materials, and selects steel slag as coarse and fine aggregate to achieve high-value utilization of industrial solid waste. 2. The present invention uses magnesium-based cementitious materials as the main material, adds ultra-fine sulfided steel slag powder and red mud for active supplementation, and the hydration products are stacked and interwoven, which has good density and fireproof effect. 3. The cementitious material of the present invention overcomes the disadvantages of low mechanical strength and poor slurry workability caused by the use of magnesium oxide desulfurization waste residue through compounding of raw materials. 4. The coarse and fine aggregates of steel slag are combined with specially composed mixed fibers and hydration products to improve the high temperature stability of the fireproof board. 5. The preparation process of the present invention is simple and has good environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the related technologies, the drawings required for use in the specific embodiments or the related technical descriptions will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 : Schematic diagram of the results of high temperature detection of various embodiments and comparative examples in the implementation mode of the present invention. DETAILED DESCRIPTION

[0022] In order to characterize the technical effect of the present invention, a fireproof board was prepared and its performance was tested. During the test, the particle size of magnesium oxide desulfurization waste slag was ≤45μm, the light-burned magnesium oxide was made by calcining magnesite at 950℃, and the particle size was ≤75μm, the heavy-burned magnesium oxide was made by calcining magnesite at 1500℃, and the particle size was ≤45μm, the ultrafine sulfided steel slag powder was made by sulfiding and grinding steel slag micropowder, and the particle size was ≤10μm, the red mud particle size was ≤75μm, the steel slag coarse aggregate particle size was 5-16mm, and the steel slag fine aggregate particle size was 0.1-0.425μm, glass fiber diameter is 10-12μm, length is 12-14mm, basalt fiber diameter is 15-16μm, length is 10-12mm, calcium sulfate whisker diameter is 2-6μm, length is 50-160μm, water reducer is polycarboxylate water reducer, performance test includes room temperature test and high temperature test, high temperature test is to heat the specimen with standard curing for 28d in 800℃ equipment for 6h, then put it to room temperature for relevant test, test results can be found in Figure 1 The mechanical properties test was carried out in accordance with GB-T17671, and the volume stability test was carried out in accordance with JGJ-T70. The fireproof board is composed of the following raw materials in parts by weight: 190 parts of magnesium oxide desulfurization waste slag, 60 parts of light-burned magnesium oxide, 90 parts of heavy-burned magnesium oxide, 110 parts of potassium dihydrogen phosphate, 56 parts of ultrafine sulfide steel slag powder, 21 parts of red mud, 1100 parts of steel slag coarse aggregate, 850 parts of steel slag fine aggregate, 5.5 parts of borax, 5 parts of glass fiber, 3 parts of basalt fiber, 4 parts of calcium sulfate whisker, 9 parts of water reducer, and 163 parts of water.

[0023] After testing, the initial fluidity of the slurry is 680mm, the workability is good, the 28d compressive strength is 43.6MPa, and after high-temperature testing, the volume change rate of the specimen is +0.05%, the mass residue is 98.3%, the compressive strength is 37.1MPa, and there is no cracking or peeling. Example

[0024] The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste slag, 70 parts of light-burned magnesium oxide, 80 parts of heavy-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of ultrafine sulfide steel slag powder, 23 parts of red mud, 1120 parts of steel slag coarse aggregate, 840 parts of steel slag fine aggregate, 6 parts of borax, 4 parts of glass fiber, 4 parts of basalt fiber, 5 parts of calcium sulfate whiskers, 10 parts of water reducer, and 163 parts of water.

[0025] After testing, the initial fluidity of the slurry was 690mm, workability was good, 28d compressive strength was 45.2MPa, and after high temperature testing, the volume change rate of the specimen was +0.03%, the mass residue was 98.6%, the compressive strength was 37.7MPa, and there was no cracking or peeling.

[0026] Comparative Example 1 The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste slag, 150 parts of light-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of ultrafine sulfide steel slag powder, 23 parts of red mud, 1120 parts of steel slag coarse aggregate, 840 parts of steel slag fine aggregate, 6 parts of borax, 4 parts of glass fiber, 4 parts of basalt fiber, 5 parts of calcium sulfate whisker, 10 parts of water reducer, and 163 parts of water.

[0027] After testing, the initial fluidity of the slurry was 620mm, the workability was general, there was stone exposure, the 28d compressive strength was 37.5MPa, and after high temperature testing, the volume change rate of the specimen was +0.11%, the mass residue was 93.1%, the compressive strength was 26.3MPa, and there was no cracking or peeling.

[0028] Comparative Example 2 The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste slag, 150 parts of dead-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of ultrafine sulfide steel slag powder, 23 parts of aluminum ash, 1120 parts of steel slag coarse aggregate, 840 parts of steel slag fine aggregate, 6 parts of borax, 4 parts of glass fiber, 4 parts of basalt fiber, 5 parts of calcium sulfate whisker, 10 parts of water reducer, and 163 parts of water.

[0029] After testing, the initial fluidity of the slurry was 590mm, the workability was general, the viscosity was high, the 28d compressive strength was 30.2MPa, and after high temperature testing, the volume change rate of the specimen was +0.16%, the mass residue was 92.6%, the compressive strength was 25.0MPa, and there were microcracks on the surface.

[0030] Comparative Example 3 The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste slag, 70 parts of light-burned magnesium oxide, 80 parts of heavy-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of ultrafine carbonized steel slag powder, 23 parts of fly ash, 1120 parts of steel slag coarse aggregate, 840 parts of steel slag fine aggregate, 6 parts of borax, 4 parts of glass fiber, 4 parts of basalt fiber, 5 parts of calcium sulfate whisker, 10 parts of water reducer, and 163 parts of water.

[0031] After testing, the initial fluidity of the slurry was 500mm, the workability was poor, it was compacted, and the 28d compressive strength was 38.1MPa. After high-temperature testing, the volume change rate of the specimen was +0.24%, the mass residue was 91.7%, the compressive strength was 21.6MPa, there were micro-cracks on the surface, and slight peeling.

[0032] Comparative Example 4 The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste residue, 150 parts of light-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of fly ash, 23 parts of mineral powder, 1120 parts of steel slag coarse aggregate, 840 parts of steel slag fine aggregate, 6 parts of borax, 6 parts of glass fiber, 6 parts of basalt fiber, 10 parts of water reducer, and 163 parts of water.

[0033] After testing, the slurry had no fluidity, and the 28d compressive strength was 32.9MPa. After high-temperature testing, the volume change rate of the specimen was +0.34%, the mass residue was 89.7%, the compressive strength was 8.2MPa, and the surface was cracked and peeling.

[0034] Comparative Example 5 The fireproof board is composed of the following raw materials in parts by weight: 200 parts of magnesium oxide desulfurization waste residue, 70 parts of light-burned magnesium oxide, 80 parts of heavy-burned magnesium oxide, 102 parts of potassium dihydrogen phosphate, 60 parts of ultrafine sulfide steel slag powder, 23 parts of red mud, 1120 parts of granite coarse aggregate, 840 parts of machine-made sand, 6 parts of borax, 13 parts of glass fiber, 10 parts of water reducer, and 163 parts of water.

[0035] After testing, the initial fluidity of the slurry is 660mm, the workability is good, the 28d compressive strength is 37.3MPa, and after high temperature testing, the volume change rate of the specimen is +0.16%, the mass residue is 91.3%, the compressive strength is 20.5MPa, and the surface is slightly peeling.

[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A fireproof board, characterized in that: It is composed of the following raw materials in parts by weight: 190-200 parts of magnesium oxide desulfurization waste residue, 50-70 parts of light-burned magnesium oxide, 70-90 parts of heavy-burned magnesium oxide, 100-110 parts of potassium dihydrogen phosphate, 50-60 parts of ultrafine sulfided steel slag powder, 20-25 parts of red mud, 1080-1120 parts of steel slag coarse aggregate, 830-850 parts of steel slag fine aggregate, 5-6 parts of borax, 4-5 parts of glass fiber, 3-4 parts of basalt fiber, 3-5 parts of calcium sulfate whisker, 7-10 parts of water reducer, 158-165 parts of water; The particle size of the magnesium oxide desulfurization waste residue is ≤45 μm.

2. The fireproof board according to claim 1, characterized in that: The light-burned magnesium oxide is prepared by calcining magnesite at 900-1000° C., and has a particle size of ≤75 μm.

3. The fireproof board according to claim 1, characterized in that: The dead-burned magnesium oxide is prepared by calcining magnesite at 1450-1500° C., and has a particle size of ≤45 μm.

4. The fireproof board according to claim 1, characterized in that: The ultrafine sulfided steel slag powder is prepared by sulfiding and grinding steel slag powder, and the particle size is ≤10 μm.

5. The fireproof board according to claim 1, characterized in that: The red mud particle size is ≤75 μm.

6. The fireproof board according to claim 1, characterized in that: The particle size of the steel slag coarse aggregate is 5-16 mm, and the particle size of the steel slag fine aggregate is 0.1-0.425 μm.

7. The fireproof board according to claim 1, characterized in that: The glass fiber has a diameter of 10-12 μm and a length of 12-14 mm, the basalt fiber has a diameter of 15-16 μm and a length of 10-12 mm, and the calcium sulfate whisker has a diameter of 2-6 μm and a length of 50-160 μm.

8. The fireproof board according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

9. The method for preparing the fireproof board according to any one of claims 1 to 8, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Mix all the raw materials evenly to obtain slurry. 3) Shape the slurry, demould and cure it.

Citation Information

Patent Citations

  • Magnesium phosphate cement prepared by using magnesium oxide byproduct in process of extracting lithium carbonate from salt lake

    CN102390943A

  • Sulfur and phosphate cement insulation mortar or insulation board

    CN102786285A

  • Process for preparing lightweight thermal-insulation magnesium phosphate cement-based material from boric sludge

    CN118439843A